Self-breathing anti-scaling cathode, preparation method, electrolytic bath and application of self-breathing anti-scaling cathode

By using a self-breathing anti-scaling cathode preparation method and a hydrophobic anode design, the problems of low H2O2 generation efficiency and electrode scaling in membrane-free electrolyzers were solved, achieving efficient and stable electrosynthesis of H2O2 and degradation of pollutants, while reducing energy consumption and operating costs.

CN121023552AActive Publication Date: 2025-11-28ZHEJIANG YIPAI TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511573520.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2025-11-28
Estimated Expiration
2045-10-31

AI Technical Summary

Technical Problem

The direct anodic oxidation degradation of H2O2 in membrane-free electrolytic cells is a serious problem, and scaling on the electrode surface leads to a decrease in the efficiency of H2O2 generation, making it difficult to achieve efficient and stable electrosynthesis of H2O2.

Method used

The preparation method of the self-breathing anti-scaling cathode involves mixing a carbon substrate with a catalyst precursor and calcining it under a protective atmosphere, spraying a hydrophobic agent, and then calcining it again under an oxygen-containing atmosphere. Combined with a hydrophobic anode design, this forms a modular electrolytic cell structure that does not require additional oxygen aeration.

Benefits of technology

It improves oxygen mass transfer efficiency, inhibits divalent ion deposition, increases H2O2 generation capacity and yield, prolongs electrode stability, reduces energy consumption and operating costs, and achieves efficient and stable electrosynthesis of H2O2 for pollutant degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121023552A_ABST
    Figure CN121023552A_ABST
Patent Text Reader

Abstract

The invention provides a self-breathing anti-scaling cathode, a preparation method, an electrolytic bath and application of the electrolytic bath, and belongs to the technical field of electrochemical electrodes. The preparation method comprises the following steps: mixing a carbon substrate and a catalyst precursor solution, and carrying out first calcination on the mixed solution under a protective atmosphere to obtain an anti-scaling cathode; and the anti-scaling cathode is sprayed with a water repellent agent and then subjected to second calcination in an oxygen-containing atmosphere, and the self-breathing type anti-scaling cathode is obtained. On one hand, the oxygen mass transfer efficiency is improved through the self-breathing anti-scaling cathode, deposition of divalent ions such as Ca < 2 + > and Mg < 2 + > is inhibited, the generation capacity of hydrogen peroxide is remarkably enhanced, and the long-term operation stability is improved; on the other hand, a spatial hydrophobic microenvironment is provided, and the yield of H2O2 is increased under the condition that external air ventilation is not needed; meanwhile, due to the design of the hydrophobic anode, decomposition of H2O2 at the anode is reduced, and efficient and stable electrosynthesis of H2O2 for pollutant degradation is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electrochemical electrode, and particularly relates to a self-breathing anti-fouling cathode, a preparation method thereof, an electrolytic cell and application thereof. BACKGROUND

[0002] Hydrogen peroxide (H2O2) is widely used in papermaking, wastewater treatment, medicine, textile and other fields as an excellent oxidant. The traditional anthraquinone method for synthesizing H2O2 in industrial production has complex process, serious pollution and high energy consumption. Based on 2e - transfer path, the driving oxygen reduction reaction (2e - ORR) for preparing H2O2 has the advantages of mild operating conditions, low voltage directly provided by renewable energy, rich oxygen raw materials, high product selectivity and high yield, and is considered as the frontier direction of electrochemical synthesis of H2O2.

[0003] However, the problem of direct anodic oxidation degradation of H2O2 in the membraneless electrolytic cell seriously limits the practical application and efficiency improvement of the technology, so that it is a key challenge to maintain high concentration of H2O2 in the membraneless electrochemical system. In addition, the fouling problem of the electrode surface further restricts the long-term stability, which is mainly caused by the deposition of Ca 2+ , Mg 2+ and other divalent ions in wastewater and the blocking of active sites caused by the local high alkalinity environment of the cathode, which finally causes significant attenuation of H2O2 generation efficiency.

[0004] Therefore, how to inhibit the decomposition of H2O2 and alleviate the electrode fouling is the core problem to be solved for realizing efficient and stable electro-synthesis of H2O2. SUMMARY

[0005] The present application aims at providing a self-breathing anti-fouling cathode, a preparation method thereof, an electrolytic cell and application thereof to solve the above problems in the prior art.

[0006] In order to achieve the above-mentioned application purposes, the present application provides the following technical solutions. The present application provides a preparation method of a self-breathing anti-fouling cathode, comprising the following steps: 1) mixing a carbon substrate and a catalyst precursor solution, and performing first calcination on the mixed solution in a protective atmosphere to obtain an anti-fouling cathode; 2) performing second calcination on the anti-fouling cathode after spraying a hydrophobic agent in an oxygen-containing atmosphere to obtain a self-breathing anti-fouling cathode; Step 1) The catalyst precursor solution is composed of a catalyst, a conductive agent, a binder solution, a surfactant solution, a scale inhibitor solution, and a dispersant; the mass ratio of the catalyst, conductive agent, binder solution, surfactant solution, scale inhibitor solution, and dispersant is 1:0.25~2:0.1~1.25:0.1~2.4:0.2~2:10~100; Step 2) The hydrophobic agent is polytetrafluoroethylene, methyltrimethoxysilane, or polydimethylsiloxane, and the spraying amount of the hydrophobic agent is 0.05~1.0 mg / cm³. 2 .

[0007] Preferably, the catalyst is prepared by dispersing carbon black in a sodium hydroxide solution and carrying out a hydrothermal reaction. The mass-to-volume ratio of carbon black to sodium hydroxide solution is 1g:600~900mL, and the concentration of sodium hydroxide solution is 0.1~12mol / L; the hydrothermal reaction temperature is 150~200℃, and the hydrothermal reaction time is 6~18h.

[0008] Preferably, the conductive agent is carbon nanotubes, carbon black, graphite, graphene, or reduced graphene oxide. The adhesive solution is one or two of polyvinylidene fluoride solution, polytetrafluoroethylene solution, and alkaline ionomer solution; the mass fraction of the alkaline ionomer solution is 5-20%, and the mass fractions of the polytetrafluoroethylene solution and the polyvinylidene fluoride solution are independently 10-60%. The surfactant solution has a mass fraction of 5-30%, and the surfactant is one or two of polyvinyl alcohol, polyvinylpyrrolidone, sodium dodecyl sulfonate, fatty alcohol polyoxyethylene ether, and polyethylene glycol. The scale inhibitor solution has a mass fraction of 5-50%, and the scale inhibitor is sodium polyphosphate, organophosphonate, sodium polyacrylate, polyepoxysuccinic acid, polymaleic anhydride, or polyaspartic acid. The dispersant is composed of water and an organic solvent, wherein the organic solvent is ethanol, isopropanol, methanol, glycerol, pentanediol, n-butanol or acetic acid; the mass fraction of water in the dispersant is 25-80%.

[0009] Preferably, the mixing method in step 1) is ultrasonication, impregnation or electrophoretic adsorption; the protective atmosphere is argon or nitrogen; and the oxygen-containing atmosphere in step 2) is high-purity oxygen, air or carbon dioxide.

[0010] Preferably, in step 1) the first calcination and step 2) the second calcination, the calcination temperature is independently 250~500℃, the calcination time is independently 0.5~2.5h, and the heating rate to the calcination temperature is independently 2~10℃ / min.

[0011] The present invention also provides a self-breathing anti-scaling cathode prepared by the above preparation method, which does not require additional oxygen aeration.

[0012] The present invention also provides an electrolytic cell comprising the aforementioned self-breathing anti-scaling cathode, the electrolytic cell comprising an anode end plate 1, a hydrophobic anode 2, an electrolyte flow chamber 4, the aforementioned self-breathing anti-scaling cathode 5, a perforated current collector 6, and a cathode end plate 7; The hydrophobic anode 2 is assembled to the anode end plate 1 through the anode terminal mounting hole 11; the self-breathing anti-scaling cathode 5 quickly engages with the hollow current collector 6 and is embedded into the cathode end plate 7 through the cathode terminal mounting hole 71; the electrolyte flow chamber 4 is provided with a reaction through hole connecting the anode end plate 1 and the cathode end plate 7. The negative end plate 7 has a hollow structure.

[0013] Preferably, the hydrophobic anode is prepared by: A titanium substrate is subjected to constant current electrodeposition and a first calcination sequentially to obtain an anode electrode; the anode electrode is then coated with a hydrophobic agent and subjected to a second calcination sequentially to obtain a hydrophobic anode. The electrolyte for constant current electrodeposition comprises a metal precursor and a solvent. The metal precursor is chloroiridium acid and ruthenium chloride, and the molar ratio of chloroiridium acid to ruthenium chloride is 1:0.2~3. The solvent is one or two of methanol, ethanol, isopropanol and n-butanol. The concentration of the metal precursor in the electrolyte is 0.1~0.5 mol / L.

[0014] Preferably, the constant current electrodeposition temperature is 1~10℃ and the current density is 5~50mA / cm². 2 The time is 10-40 minutes; The first calcination temperature is 400~500℃, the time is 0.5~2h, and the heating rate to the first calcination temperature is 2~10℃ / min; the second calcination temperature is 250~500℃, the time is 0.5~2.5h, and the heating rate to the second calcination temperature is 2~10℃ / min. The hydrophobic agent is polytetrafluoroethylene, methyltrimethoxysilane, or polydimethylsiloxane, and the spraying amount of the hydrophobic agent is 0.05~1.0 mg / cm³. 2 .

[0015] The present invention also provides the application of the electrolytic cell in the degradation and removal of pollutants in water bodies.

[0016] The beneficial effects of this invention are: 1) The electrolytic cell of this invention adopts a membrane-free design to reduce energy consumption and cost. On the one hand, it improves oxygen mass transfer efficiency and inhibits calcium buildup through a self-breathing anti-fouling cathode. 2+ Mg 2+The deposition of divalent ions significantly enhances the generation capacity of hydrogen peroxide and improves long-term operational stability. On the other hand, it has a hydrophobic microenvironment, which increases the production of H2O2 without the need for external air ventilation. At the same time, the hydrophobic anode design reduces the decomposition of H2O2 at the anode, enabling efficient and stable electrosynthesis of H2O2 for pollutant degradation.

[0017] 2) The threaded internal structure design of the electrolyzer enables the replacement of the self-breathing anti-scaling cathode, which has significant practical advantages: First, the modular electrode structure allows for rapid replacement of deactivated cathodes, significantly reducing system downtime for maintenance compared to traditional fixed electrodes, ensuring process continuity, reducing operating costs, and not affecting the anode and other components; Second, the electrolyzer of this invention allows for flexible matching of the optimal anti-scaling cathode material (such as catalyst loading) according to water quality characteristics (such as hardness and organic matter content), achieving dynamic optimization of H2O2 yield and pollutant removal efficiency; This innovative design not only improves the system's economy and adaptability but also provides a key solution for commercialization. Attached Figure Description

[0018] Figure 1 Linear scan voltammetry curves of the self-breathing anti-scaling cathodes prepared under different conditions in Example 1 and Comparative Examples 1-2; Figure 2 The amount of hydrogen peroxide generated (a), Faraday efficiency (b), and scale amount (c) before and after the self-breathing anti-scaling cathode reaction prepared under different conditions in Examples 1 and Comparative Examples 1-2 are shown. Figure 3 This is a schematic diagram of an electrolytic cell using the self-breathing anti-scaling cathode prepared in Example 1 for Application Example 1; wherein, 1 is the anode end plate, 2 is the hydrophobic anode, 3 is the first gasket, 4 is the electrolyte flow chamber, 5 is the self-breathing anti-scaling cathode, 6 is the perforated current collector, 7 is the cathode end plate, 11 is the anode terminal mounting hole, 12 is the anode internal thread structure, 31 is the second gasket, 32 is the third gasket, 41 is the electrolyte inlet, 42 is the electrolyte outlet, 43 is the external thread interface, 71 is the cathode terminal mounting hole, and 72 is the cathode internal thread structure; Figure 4 To apply the self-breathing anti-scaling cathode prepared in Example 1 to the electrolytic cells of Examples 1 and 2, and in combination with different anode electrodes, at 100 mA / cm 2 The relationship curves between hydrogen peroxide generation (a), Faraday efficiency (b), and pollutant removal (c) after continuous reaction at current density. Detailed Implementation

[0019] This invention provides a method for preparing a self-breathing anti-scaling cathode, comprising the following steps: 1) The carbon substrate and catalyst precursor solution are mixed, and the mixture is calcined for the first time under a protective atmosphere to obtain an anti-scaling cathode; 2) After the anti-scaling cathode is sprayed with a hydrophobic agent, it is subjected to a second calcination in an oxygen-containing atmosphere to obtain a self-breathing anti-scaling cathode; Step 1) The catalyst precursor solution is composed of a catalyst, a conductive agent, a binder solution, a surfactant solution, a scale inhibitor solution, and a dispersant; the mass ratio of the catalyst, conductive agent, binder solution, surfactant solution, scale inhibitor solution, and dispersant is 1:0.25~2:0.1~1.25:0.1~2.4:0.2~2:10~100; Step 2) The hydrophobic agent is polytetrafluoroethylene, methyltrimethoxysilane, or polydimethylsiloxane, and the spraying amount of the hydrophobic agent is 0.05~1.0 mg / cm³. 2 .

[0020] In this invention, the mass ratio of the catalyst, conductive agent, binder solution, surfactant solution, scale inhibitor solution and dispersant is preferably 1:0.5~1.5:0.25~1:0.5~2:0.5~1.5:20~90, more preferably 1:0.8~1.2:0.4~0.9:0.8~1.5:0.75~1.2:30~80, and even more preferably 1:1:0.7~0.8:1~1.2:1:50.

[0021] In this invention, the preferred method for preparing the catalyst is to disperse carbon black in a sodium hydroxide solution and carry out a hydrothermal reaction. The preferred mass-to-volume ratio of carbon black to sodium hydroxide solution is 1g:600-900mL, more preferably 1g:650-850mL, and even more preferably 1g:700-800mL. The preferred concentration of sodium hydroxide solution is 0.1-12mol / L, more preferably 1-10mol / L, and even more preferably 3-7mol / L. The preferred temperature of the hydrothermal reaction is 150-200℃, more preferably 160-190℃, and even more preferably 170-180℃. The preferred time of the hydrothermal reaction is 6-18h, more preferably 8-15h, and even more preferably 10-12h.

[0022] In this invention, the product of the hydrothermal reaction is preferably washed with ethanol until the supernatant is neutral before being sequentially filtered and dried; the vacuum degree of filtration is preferably 0.07~0.09MPa, more preferably 0.08MPa, the drying temperature is preferably 55~65℃, more preferably 60℃, and the drying time is preferably 8~16h, more preferably 10~14h, and more preferably 12h.

[0023] In this invention, the conductive agent is preferably carbon nanotubes, carbon black, graphite, graphene, or reduced graphene oxide. The adhesive solution is preferably one or two of polyvinylidene fluoride solution, polytetrafluoroethylene solution, and alkaline ionomer solution; the mass fraction of the alkaline ionomer solution is preferably 5-20%, more preferably 8-16%, and even more preferably 10-15%; the mass fractions of the polytetrafluoroethylene solution and the polyvinylidene fluoride solution are preferably 10-60%, more preferably 20-50%, and even more preferably 30-40%; The surfactant solution preferably has a mass fraction of 5-30%, more preferably 10-25%, and even more preferably 15-20%. The surfactant is preferably one or two of polyvinyl alcohol, polyvinylpyrrolidone, sodium dodecyl sulfonate, fatty alcohol polyoxyethylene ether, and polyethylene glycol. The scale inhibitor solution preferably has a mass fraction of 5-50%, more preferably 10-45%, and even more preferably 15-40%. The scale inhibitor is preferably sodium polyphosphate, organophosphonate, sodium polyacrylate, polyepoxysuccinic acid, polymaleic anhydride, or polyaspartic acid. The dispersant is preferably composed of water and an organic solvent, wherein the organic solvent is preferably ethanol, isopropanol, methanol, glycerol, pentanediol, n-butanol or acetic acid; the mass fraction of water in the dispersant is preferably 25-80%, more preferably 35-70%, and more preferably 45-60%.

[0024] In this invention, the solvent of the adhesive solution is pure water, the solvent of the surfactant solution is isopropanol, and the solvent of the scale inhibitor solution is a mixture of pure water and isopropanol, wherein the mass ratio of pure water to isopropanol in the mixture is 2:1.

[0025] In this invention, the molecular weight of polyvinyl alcohol is preferably 31,000 to 50,000.

[0026] In this invention, when there are two types of adhesive solutions, the mass ratio of the first adhesive solution to the second adhesive solution is preferably 1~5:1~7, more preferably 1~3:1~3; in the adhesive solution, the alkaline ionomer is preferably Sustainion® XA-9, Sustainion® XB-7, Sustainion® XC-2 or Fumion FAA-3-SOLUT-10; when there are two types of surfactant solutions, the mass ratio of the first surfactant solution to the second surfactant solution is preferably 1~10:1~10, more preferably 1~9:1~9, and more preferably 1~7:1~7.

[0027] In this invention, the mixing method in step 1) is preferably ultrasonic, impregnation or electrophoretic adsorption; the protective atmosphere is preferably argon or nitrogen; and the oxygen-containing atmosphere in step 2) is preferably high-purity oxygen, air or carbon dioxide.

[0028] In this invention, in step 1) the first calcination and step 2) the second calcination, the calcination temperature is preferably 250~500℃, more preferably 300~450℃, and even more preferably 350~410℃. The calcination time is preferably 0.5~2.5h, more preferably 1~2h, and even more preferably 1.5h. The heating rate to the calcination temperature is preferably 2~10℃ / min, more preferably 4~8℃ / min, and even more preferably 5~6℃ / min.

[0029] In this invention, the preferred spraying amount of the hydrophobic agent in step 2) is 0.05~1.0 mg / cm³. 2 More preferably, it is 0.1~0.8 mg / cm³. 2 More preferably, it is 0.4~0.6 mg / cm³. 2 .

[0030] The present invention also provides a self-breathing anti-scaling cathode prepared by the above preparation method, which does not require additional oxygen aeration.

[0031] The present invention also provides an electrolytic cell for a self-breathing anti-scaling cathode, the electrolytic cell comprising an anode end plate 1, a hydrophobic anode 2, a first gasket 3, an electrolyte flow chamber 4, a second gasket 31, the self-breathing anti-scaling cathode 5, a perforated current collector 6, a third gasket 32, and a cathode end plate 7. The hydrophobic anode 2 is assembled to the anode end plate 1 through the anode terminal mounting hole 11; the self-breathing anti-scaling cathode 5 quickly engages with the hollow current collector 6 and is embedded into the cathode end plate 7 through the cathode terminal mounting hole 71; the electrolyte flow chamber 4 is provided with a reaction through hole connecting the anode end plate 1 and the cathode end plate 7. The negative end plate 7 has a hollow structure.

[0032] In this invention, the anode end plate 1 is provided with an anode terminal mounting hole 11 and an anode internal thread structure 12; the cathode end plate 7 is designed with a hollow structure to allow air to pass through, and is correspondingly configured with a cathode terminal mounting hole 71 and a cathode internal thread structure 72; the electrolyte flow chamber 4 is provided with a reaction through hole connecting the anode end plate 1 and the cathode end plate 7, and the reaction through hole continuously pumps the wastewater to be treated into the electrolyte inlet 41 through a peristaltic pump, and discharges the treated wastewater into the outlet 42; the reaction through hole is a circular opening located in the center of the electrolyte flow chamber, and the size of the circular opening is preferably 5~25cm×5~25cm, more preferably 6~20cm×6cm. The length is approximately 20 cm, more preferably 8-18 cm × 8-18 cm, and both sides are provided with external threaded interface structures 43; the electrolyte flow chamber 4 is quickly matched and connected to the cathode internal thread structure 72 on the cathode end plate 7 through the external threaded interface structure 43 via a precisely designed threaded interface structure; similarly, the electrolyte flow chamber 4 is quickly matched and connected to the anode internal thread structure 12 on the anode end plate 1 through the external threaded interface structure 43 via a precisely designed threaded interface structure; the rotation speed of the peristaltic pump is preferably 50-500 r / min, more preferably 100-400 r / min, and more preferably 200-300 r / min.

[0033] In this invention, the preferred method for preparing the hydrophobic anode is as follows: A titanium substrate is subjected to constant current electrodeposition and a first calcination sequentially to obtain an anode electrode; the anode electrode is then coated with a hydrophobic agent and subjected to a second calcination sequentially to obtain a hydrophobic anode. The electrolyte for constant current electrodeposition preferably comprises a metal precursor and a solvent. The metal precursor is preferably chloroiridium acid and ruthenium chloride, and the molar ratio of chloroiridium acid to ruthenium chloride is preferably 1:0.2~3, more preferably 1:0.5~2.5, and even more preferably 1:1~2. The solvent is preferably one or two of methanol, ethanol, isopropanol, and n-butanol. The concentration of the metal precursor in the electrolyte is preferably 0.1~0.5 mol / L, more preferably 0.2~0.4 mol / L, and even more preferably 0.3 mol / L.

[0034] In this invention, when the solvent in constant current electrodeposition is any two types, the volume ratio of the two solvents is preferably 1:1 to 5, more preferably 1:1 to 2, and even more preferably 1:1.

[0035] In this invention, the temperature for constant current electrodeposition is preferably 1~10℃, more preferably 3~8℃, and even more preferably 5~6℃, and the current density is preferably 5~50mA / cm². 2 Further preferred is 10~40 mA / cm 2 More preferably 20~30 mA / cm 2The preferred time is 10-40 min, more preferably 20-30 min, and even more preferably 25 min; The preferred temperature for the first calcination is 400-500℃, more preferably 420-480℃, and even more preferably 450-460℃. The preferred time is 0.5-2h, more preferably 0.75-1.5h, and even more preferably 1-1.25h. The preferred heating rate to the first calcination temperature is 2-10℃ / min, more preferably 4-8℃ / min, and even more preferably 5-6℃ / min. The preferred temperature for the second calcination is 250-500℃, more preferably 300-450℃, and even more preferably 350-400℃. The preferred time is 0.5-2.5h, more preferably 1-2h, and even more preferably 1.5h. The preferred heating rate to the second calcination temperature is 2-10℃ / min, more preferably 4-8℃ / min, and even more preferably 5-6℃ / min. The hydrophobic agent is preferably polytetrafluoroethylene, methyltrimethoxysilane, or polydimethylsiloxane, and the preferred application rate of the hydrophobic agent is 0.05~1.0 mg / cm³. 2 More preferably, it is 0.1~0.8 mg / cm³. 2 More preferably, it is 0.4~0.6 mg / cm³. 2 .

[0036] In this invention, the contact angle of the hydrophobic anode is preferably 130~150°, more preferably 135~145°, and even more preferably 140°.

[0037] The present invention also provides the application of the electrolytic cell in the degradation and removal of pollutants in water bodies.

[0038] The present invention does not impose any special limitations on the method of application described herein; it may be applied in accordance with methods known in the art.

[0039] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0040] The catalyst used in the examples and comparative examples was prepared as follows: 1g of carbon black was dispersed in 700mL of a 6mol / L sodium hydroxide aqueous solution and hydrothermally reacted in a reactor at 180℃ for 12h. After the reaction was completed, the supernatant was washed with ethanol (the volume ratio of anhydrous ethanol to deionized water was 1:1) until it was neutral. Then, it was filtered under a vacuum of 0.08MPa and finally dried at 60℃ for 12h.

[0041] The alkaline ionomer is Sustainion® XC-2; the carbon substrate is SGL porous carbon fiber felt GFD 4.65 EA (4.6 mm thick).

[0042] Example 1

[0043] Using graphite as a conductive agent, a polytetrafluoroethylene solution (10% by mass) and an alkaline ionomer solution (5% by mass) in a mass ratio of 3:1 were used as binders. A 5% polyvinyl alcohol solution (molecular weight 40,000) was used as a surfactant. A 20% polyepoxysuccinic acid solution (relative molecular weight 1,000) was used as a scale inhibitor. A mixture of water and isopropanol (70% by mass of water) was used as a dispersant. The catalyst, conductive agent, binder solution, surfactant solution, scale inhibitor solution, and dispersant were mixed in a mass ratio of 1:1:0.4:0.8:0.6:80. The mixture was stirred at 200 rpm for 60 min and then ball-milled at 500 rpm for 4 h (using agate ball milling beads) to obtain the catalyst precursor solution. The catalyst precursor solution was electrophoretically adsorbed onto a carbon substrate. The specific electrophoretic adsorption process was as follows: the carbon substrate was immersed in the catalyst precursor solution, a platinum mesh was used as the counter electrode and placed 2 cm away from the working electrode, and both electrodes were connected to a DC power supply with a voltage of 30V applied for 30 min. After completion, the resulting electrode was dried overnight in an oven at 60℃. Then, it was placed in a nitrogen atmosphere and heated to 350℃ at a rate of 5℃ / min, and calcined at 350℃ for 1 h to obtain an anti-scaling cathode. Subsequently, polytetrafluoroethylene (PTFE) was sprayed onto one side of the anti-scaling cathode at a loading of 1.0 mg / cm³. 2 Finally, it was placed in an air atmosphere and heated to 350°C at a heating rate of 5°C / min, and calcined at 350°C for 1 hour to obtain a self-breathing anti-scaling cathode.

[0044] Example 2

[0045] Carbon black was used as the conductive agent. A 1:1 mixture of polytetrafluoroethylene (PTFE) solution (10% by mass) and polyvinylidene fluoride (PVDF) solution (15% by mass) was used as the binder solution. A 15% polyvinylpyrrolidone (PVP) solution was used as the surfactant solution. A 15% polyaspartic acid (PA) solution was used as the scale inhibitor solution. A mixture of water and glycerol (50% water by mass) was used as the dispersant. The catalyst, conductive agent, binder solution, surfactant solution, scale inhibitor solution, and dispersant were mixed in a mass ratio of 1:0.5:0.2:0.5:1.6:60. After stirring for 60 min, the mixture was ball-milled for 4 h to obtain the catalyst precursor solution. The catalyst precursor solution was ultrasonically dispersed onto a carbon substrate at a frequency of 40 kHz for 30 min at a temperature of 8 °C. The substrate was then placed in a nitrogen atmosphere and heated to 300 °C at a rate of 3 °C / min. The substrate was calcined at 300 °C for 2 h to obtain an anti-scaling cathode. Subsequently, methyltrimethoxysilane was sprayed onto the anti-scaling cathode side at a loading of 0.5 mg / cm³. 2Finally, it was placed in an air atmosphere and heated to 350°C at a heating rate of 3°C / min, and calcined at 350°C for 1 hour to obtain a self-breathing anti-scaling cathode.

[0046] Example 3

[0047] Using graphene as a conductive agent, a 20% (w / w) polytetrafluoroethylene (PTFE) solution as a binder, a 10% (w / w) sodium dodecyl sulfonate solution as a surfactant, a 25% (w / w) polymaleic anhydride solution as a scale inhibitor, and a mixture of water and n-butanol (40% (w / w)) as a dispersant, the catalyst, conductive agent, binder, surfactant, scale inhibitor, and dispersant were mixed in a mass ratio of 1:1.5:1:1.8:0.8:70. After stirring for 60 min, the mixture was ball-milled for 4 h to obtain a catalyst precursor solution. The catalyst precursor solution was impregnated onto a carbon substrate. The substrate was then placed in a nitrogen atmosphere and heated to 450 °C at a rate of 7 °C / min, and calcined at 450 °C for 0.5 h to obtain an anti-scaling cathode. Subsequently, PTFE was sprayed onto one side of the anti-scaling cathode at a loading of 0.3 mg / cm³. 2 Finally, it was transferred to a high-purity oxygen atmosphere and heated to 400°C at a heating rate of 7°C / min. It was then calcined at 400°C for 0.5 hours to obtain a self-breathing anti-scaling cathode.

[0048] Comparative Example 1

[0049] Carbon nanotubes were used as the conductive agent, a 10% polytetrafluoroethylene (PTFE) solution as the binder, a 20% polyethylene glycol (molecular weight 400) solution as the surfactant, and a mixture of water and isopropanol (70% water) as the dispersant. The catalyst, conductive agent, binder, surfactant, and dispersant were mixed in a mass ratio of 1:1:0.25:0.8:80. After stirring for 60 min, the mixture was ball-milled for 4 h to obtain the catalyst precursor solution. The catalyst precursor solution was impregnated onto a carbon substrate. The substrate was then placed in a nitrogen atmosphere and heated to 410 °C at a rate of 5 °C / min, and calcined at 410 °C for 1 h to obtain an anti-scaling cathode. Subsequently, PTFE was sprayed onto one side of the anti-scaling cathode at a loading of 0.8 mg / cm³. 2 Finally, it was placed in an air atmosphere and heated to 350°C at a heating rate of 5°C / min, and calcined at 350°C for 1 hour to obtain a self-breathing anti-scaling cathode.

[0050] Comparative Example 2

[0051] Using reduced graphene oxide as a conductive agent, a 1:1 solution of polytetrafluoroethylene (PTFE) (10% by mass) and a 5% solution of perfluorosulfonic acid naphthol (5% by mass) were used as binders. A 10% solution of fatty alcohol polyoxyethylene ether (315% by mass) was used as a surfactant, and a mixture of water and isopropanol (60% by mass of water) was used as a dispersant. The catalyst, conductive agent, binder solution, surfactant solution, and dispersant were mixed in a mass ratio of 1:1:0.5:0.6:70. After stirring the mixture for 60 min, it was ball-milled for 4 h to obtain a catalyst precursor solution. The catalyst precursor solution was ultrasonically transferred onto a carbon substrate. Then, it was placed in a nitrogen atmosphere and heated to 250 °C at a rate of 5 °C / min, and calcined at 250 °C for 1 h to obtain an anti-scaling cathode. Subsequently, PTFE was sprayed onto one side of the anti-scaling cathode at a loading of 0.75 mg / cm³. 2 Finally, it was placed in an air atmosphere and heated to 350°C at a heating rate of 5°C / min, and calcined at 350°C for 1 hour to obtain a self-breathing anti-scaling cathode.

[0052] The linear sweep voltammetric curves of the self-breathing anti-scaling cathodes prepared under different conditions in Examples 1 and Comparative Examples 1-2 are shown below. Figure 1 As shown, the linear sweep voltammetry curves were obtained from electrochemical performance testing in an H-type tank and 0.1M Na₂SO₄ solution; from Figure 1 It can be seen that the limiting current density is Example 1 ≈ Comparative Example 1 > Comparative Example 2.

[0053] Although the adsorption of scale inhibitor molecules on the catalyst surface may cover some reactive sites, dual activity compensation is achieved through the synergistic design of multiple binders: on the one hand, the Sustainion® XC-2 alkaline ionomer achieves OH... - The high efficiency of conduction facilitates the exposure of the catalytic interface that is obscured by the scale inhibitor; on the other hand, the polytetrafluoroethylene (PTFE) constructs a through-hole porous framework, which endows the electrode with excellent mechanical strength while improving the oxygen mass transfer rate, thus exhibiting a limiting current density of Example 1 ≈ Comparative Example 1. Compared with perfluorosulfonyl naphthol, the basic ionomer of Sustainion® XC-2 is more conducive to the two-electron oxygen reduction reaction.

[0054] The hydrogen peroxide generation (a), Faraday efficiency (b), and scale accumulation (c) of the self-breathing anti-scaling cathodes prepared under different conditions in Examples 1 and 1-2 are as follows: Figure 2 As shown, the reaction occurred in 100 mL of tap water with a conductivity of 900 μS / cm at a rate of 10 mA / cm. 2 The current density was operated for 30 minutes.

[0055] from Figure 2As shown in Part a, the hydrogen peroxide production in Example 1 was 20.6227 mg / L, which was higher than that in Comparative Example 1 (14.2425 mg / L) and Comparative Example 2 (11.5607 mg / L). After 150 hours of testing, the hydrogen peroxide production in Example 1 was 17.9818 mg / L, which was higher than that in Comparative Example 1 (5.5773 mg / L) and Comparative Example 2 (1.8136 mg / L), indicating that Example 1 has excellent ORR activity and stability in tap water.

[0056] from Figure 2 As shown in Part b, the Faraday efficiency of Example 1 was 65.03%, higher than that of Comparative Example 1 (44.91%) and Comparative Example 2 (36.45%). After 150 hours of testing, the Faraday efficiency was 56.70%, higher than that of Comparative Example 1 (17.59%) and Comparative Example 2 (5.72%), indicating that Example 1 has excellent ORR activity and selectivity in tap water. This is because Example 1 used the binder Sustainion® XC-2 basic ionomer in a Ca-containing environment. 2+ / Mg 2+ In water treatment scenarios involving divalent ions, the electrostatic repulsion mechanism of their quaternary ammonium groups blocks Ca2+. 2+ / Mg 2+ The proximity of the alkaline ionomers, which primarily conduct hydroxyl radicals, facilitates the formation of a locally high-pH alkaline environment, leading to increased surface CO32- concentration. 2- / OH - An increased proportion accelerates CO3 2- Hydrolysis occurs, forming soluble Ca(HCO3)2 instead of CaCO3 precipitate, thus reducing the risk of scaling. Furthermore, the localized alkaline environment favors the two-electron oxygen reduction reaction, resulting in higher hydrogen peroxide production and Faraday efficiency. In Comparative Example 2, when perfluorosulfonyl naphthol is used, its sulfonate groups readily electrostatically adsorb Ca... 2+ / Mg 2+ The formation of sulfonate precipitates, and the fact that perfluorosulfonate naphthol mainly conducts hydrogen ions, makes the surface of the cathode electrode locally acidic, which is not conducive to the two-electron oxygen reduction reaction, thus resulting in poor hydrogen peroxide production and Faraday efficiency.

[0057] from Figure 2 As shown in section c, after 150 hours of operation, the amount of scale on the surface of Example 1 was 0.3702g, which was significantly lower than that of Comparative Example 1 (0.9826g) and Comparative Example 2 (1.1274g), indicating that the introduction of scale inhibitor can further reduce the amount of scale and extend the service life of the cathode electrode.

[0058] Application Example 1

[0059] like Figure 3As shown, the electrolytic cell consists of an anode end plate 1, a hydrophobic anode 2, a first gasket 3, an electrolyte flow chamber 4, a second gasket 31, a self-breathing anti-scaling cathode 5 (as described in Example 1), a perforated current collector 6, a third gasket 32, and a cathode end plate 7. The anode end plate 1 has an anode terminal mounting hole 11 and an anode internal thread structure 12; the hydrophobic anode 2 is assembled to the anode end plate 1 through the anode terminal mounting hole 11; the cathode end plate 7 adopts a perforated structure design to allow air to pass through, and is correspondingly equipped with a cathode terminal mounting hole 71 and a cathode internal thread structure 72. In Example 1, the self-breathing anti-scaling cathode 5 and the perforated current collector 6 quickly engage and are embedded into the cathode end plate 7 through the cathode terminal mounting hole 71. The electrolyte flow chamber 4 is provided with a reaction through hole connecting the anode end plate 1 and the cathode end plate 7. The reaction through hole continuously pumps wastewater (containing trichloroacetaldehyde, with an initial concentration of 15 mg / L) into the electrolyte inlet 41 through a peristaltic pump (speed of 200 r / min), and discharges the treated wastewater through the outlet 42. The reaction through hole is a circular opening located in the center of the electrolyte flow chamber, with a size of 5 cm × 5 cm, and external thread interface structures 43 are provided on both the left and right sides. The electrolyte flow chamber 4 is quickly matched and connected to the cathode internal thread structure 72 on the cathode end plate 7 through the external thread interface structure 43 via a precisely designed thread interface structure. Similarly, the electrolyte flow chamber 4 is quickly matched and connected to the anode internal thread structure 12 on the anode end plate 1 through the external thread interface structure 43 via a precisely designed thread interface structure.

[0060] Preparation of hydrophobic anode 2: The metal precursor was chloroiridic acid and ruthenium chloride in a molar ratio of 1:2, and the solvent was anhydrous ethanol and n-butanol in a volume ratio of 1:1. The metal precursor and solvent were mixed evenly to obtain an electrolyte with a metal precursor concentration of 0.2 mol / L. The electrolyte was then incubated at a temperature of 4℃ and a current density of 30 mA / cm². 2 Under constant current electrodeposition conditions, a uniform growth was performed on a titanium substrate for 30 min. After electrodeposition, the substrate was dried in an oven and then transferred to a muffle furnace for calcination. The temperature was increased to 450°C at a rate of 5°C / min, and calcined at 450°C for 1 h to obtain the anode electrode. Subsequently, polytetrafluoroethylene (PTFE) was sprayed onto the surface of the anode electrode at a loading of 0.75 mg / cm³. 2 Finally, it was placed in an air atmosphere and heated to 350°C at a rate of 5°C / min, and calcined at 350°C for 1 hour to obtain a hydrophobic anode.

[0061] The above-mentioned electrolytic cell is used to remove pollutants from wastewater: Wastewater to be treated is circulated into the electrolyte flow chamber at a flow rate of 50 mL / min. The integrated design of the self-breathing anti-scaling cathode and the hollow structure on the cathode end plate forms a stable three-phase interface between oxygen in the air, water in the electrolyte flow chamber, and the catalyst on the electrode surface, achieving efficient and stable synthesis of H2O2. The hydrophobic porous layer on the hydrophobic anode surface hinders the transfer of H2O2 to the anode active site, reducing direct contact between H2O2 and the electrode, thereby inhibiting the degradation of H2O2 on the anode and achieving efficient removal of pollutants. If the self-breathing anti-scaling cathode experiences catalyst poisoning due to prolonged operation in wastewater, a threaded internal interface design allows for rapid replacement of the cathode electrode, ensuring process continuity and reducing operating costs.

[0062] Application Example 1: A schematic diagram of an electrolytic cell using the self-breathing anti-scaling cathode prepared in Example 1 is shown below. Figure 3 As shown; from Figure 3 As can be seen, the self-breathing anti-scaling cathode 5 of Example 1 quickly engages with the hollow current collector 6 and is embedded into the cathode end plate 7 through the cathode terminal mounting hole 71; and the electrolyte flow cavity 4 is quickly matched and connected through the external thread interface structure 43 and the cathode internal thread structure 72 on the cathode end plate 7 through a precisely designed thread interface structure, thereby realizing the rapid replacement of the failed cathode electrode.

[0063] Application Example 2

[0064] The only difference is that the hydrophobic anode in Application Example 1 is replaced with an anode electrode, while all other conditions remain the same as in Application Example 1.

[0065] Preparation of the anode electrode: The metal precursor was a chloroiridic acid and ruthenium chloride in a molar ratio of 1:1, and the solvent was n-butanol. The metal precursor and solvent were mixed evenly to obtain an electrolyte with a metal precursor concentration of 0.135 mol / L. The electrolyte was then incubated at a temperature of 4℃ and a current density of 35 mA / cm². 2 Under constant current electrodeposition conditions, the material was uniformly grown on a titanium substrate for 30 min. After electrodeposition, the material was dried in an oven and then transferred to a muffle furnace for calcination. The temperature was increased to 400℃ at a rate of 5℃ / min and calcined at 400℃ for 1.5 h to obtain the anode electrode.

[0066] Application Examples 1-2: Electrolytic cells using the self-breathing anti-scaling cathode prepared in Example 1, combined with different anode electrodes, at 0.1M Na2SO4 aqueous solution and 100mA / cm 2 The relationship curves (c) between hydrogen peroxide production (a), Faraday efficiency (b), and pollutant removal after the reaction at current density are shown below. Figure 4 As shown; from Figure 4As can be seen from Part a, in Application Example 1, after 10 minutes of continuous electrolysis using a hydrophobic anode, the H2O2 accumulation reached 412.61 mg / L, and further increased to 1180.13 mg / L after 30 minutes. Compared to Application Example 2, which used an unmodified anode electrode, this significantly increased the H2O2 accumulation. In Application Example 2, after 10 minutes of continuous electrolysis using an unmodified anode electrode, the H2O2 accumulation reached 280.55 mg / L, and reached 447.31 mg / L after 30 minutes.

[0067] from Figure 4 As can be seen from Part b, in Application Example 1, the hydrophobic anode used for continuous electrolysis for 10 min achieved a Faraday efficiency of 86.73%, and after 30 min, the Faraday efficiency was 82.69%. In Application Example 2, the unmodified anode electrode used for continuous electrolysis for 10 min achieved a Faraday efficiency of 58.97%, and after 30 min, the Faraday efficiency was 33.44%. This indicates that coating the anode electrode with a hydrophobic porous layer effectively reduces the contact between H2O2 and the electrode surface, thereby reducing the direct degradation of H2O2 on the anode.

[0068] from Figure 4 As can be seen from Part c, the hydrophobic anode used in Application Example 1 achieved a removal rate of 76.2% for the pollutant trichloroacetaldehyde after 10 minutes, which was significantly higher than that of the unmodified anode electrode used in Application Example 2 (55.70%). This indicates that the H2O2 accumulation in Application Example 1 was higher than that in Application Example 2, and the pollutant degradation rate was faster.

[0069] The self-breathing anti-scaling cathode of this invention improves oxygen utilization efficiency through self-breathing while eliminating the need for aeration, thus reducing energy consumption. Furthermore, by adding scale inhibitors and binders to the catalyst precursor solution, it effectively inhibits calcium deposition. Mg The deposition of divalent metal ions on the electrode surface significantly reduces the risk of scaling, improves the efficiency of hydrogen peroxide generation, and extends electrode lifespan. Simultaneously, the self-breathing electrode provides a hydrophobic microenvironment, greatly enhancing the mass transfer efficiency of oxygen from the gas phase to the catalytically active sites. The synergistic effect of these two factors significantly increases the hydrogen peroxide generation rate. In addition to integrating the aforementioned self-breathing anti-scaling cathode, the electrolyzer of this invention introduces an innovative hydrophobic anode design, which reduces the decomposition of hydrogen peroxide caused by direct anode oxidation, thus reducing hydrogen peroxide consumption more effectively. Furthermore, the cathode electrode utilizes a threaded internal interface design for rapid replacement, solving the catalyst poisoning problem during long-term operation and ultimately achieving rapid decomposition of contaminants.

[0070] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a self-breathing anti-scaling cathode, characterized in that, It includes the following steps: 1) The carbon substrate and catalyst precursor solution are mixed, and the mixture is calcined for the first time under a protective atmosphere to obtain an anti-scaling cathode; 2) After the anti-scaling cathode is sprayed with a hydrophobic agent, it is subjected to a second calcination in an oxygen-containing atmosphere to obtain a self-breathing anti-scaling cathode; Step 1) The catalyst precursor solution is composed of a catalyst, a conductive agent, a binder solution, a surfactant solution, a scale inhibitor solution, and a dispersant; the mass ratio of the catalyst, conductive agent, binder solution, surfactant solution, scale inhibitor solution, and dispersant is 1:0.25~2:0.1~1.25:0.1~2.4:0.2~2:10~100; Step 2) The hydrophobic agent is polytetrafluoroethylene, methyltrimethoxysilane, or polydimethylsiloxane, and the spraying amount of the hydrophobic agent is 0.05~1.0 mg / cm³. 2 .

2. The method for preparing the self-breathing anti-scaling cathode according to claim 1, characterized in that, The catalyst is prepared by dispersing carbon black in a sodium hydroxide solution and carrying out a hydrothermal reaction. The mass-to-volume ratio of carbon black to sodium hydroxide solution is 1g:600~900mL, and the concentration of sodium hydroxide solution is 0.1~12mol / L; the hydrothermal reaction temperature is 150~200℃, and the hydrothermal reaction time is 6~18h.

3. The method for preparing the self-breathing anti-scaling cathode according to claim 1 or 2, characterized in that, The conductive agent is carbon nanotubes, carbon black, graphite, graphene, or reduced graphene oxide. The adhesive solution is one or two of polyvinylidene fluoride solution, polytetrafluoroethylene solution, and alkaline ionomer solution; the mass fraction of the alkaline ionomer solution is 5-20%, and the mass fractions of the polytetrafluoroethylene solution and the polyvinylidene fluoride solution are independently 10-60%. The surfactant solution has a mass fraction of 5-30%, and the surfactant is one or two of polyvinyl alcohol, polyvinylpyrrolidone, sodium dodecyl sulfonate, fatty alcohol polyoxyethylene ether, and polyethylene glycol. The scale inhibitor solution has a mass fraction of 5-50%, and the scale inhibitor is sodium polyphosphate, organophosphonate, sodium polyacrylate, polyepoxysuccinic acid, polymaleic anhydride, or polyaspartic acid. The dispersant is composed of water and an organic solvent, wherein the organic solvent is ethanol, isopropanol, methanol, glycerol, pentanediol, n-butanol or acetic acid; the mass fraction of water in the dispersant is 25-80%.

4. The method for preparing the self-breathing anti-scaling cathode according to claim 3, characterized in that, Step 1) The mixing method is ultrasound, impregnation or electrophoretic adsorption; the protective atmosphere is argon or nitrogen; Step 2) The oxygen-containing atmosphere is high-purity oxygen, air or carbon dioxide.

5. The method for preparing the self-breathing anti-scaling cathode according to claim 4, characterized in that, In step 1) the first calcination and step 2) the second calcination, the calcination temperature is independently 250~500℃, the calcination time is independently 0.5~2.5h, and the heating rate to the calcination temperature is independently 2~10℃ / min.

6. The self-breathing anti-scaling cathode prepared by the preparation method according to any one of claims 1 to 5, characterized in that, Self-breathing anti-fouling cathodes do not require additional oxygenation.

7. An electrolytic cell comprising the self-breathing anti-scaling cathode as described in claim 6, characterized in that, The electrolytic cell includes an anode plate (1), a hydrophobic anode (2), an electrolyte flow chamber (4), a self-breathing anti-scaling cathode (5) as described in claim 6, a perforated current collector (6), and a cathode plate (7). The hydrophobic anode (2) is assembled to the anode end plate (1) through the anode terminal mounting hole (11); The self-breathing anti-scaling cathode (5) quickly engages with the hollow current collector (6) and is embedded into the cathode end plate (7) through the cathode terminal mounting hole (71); the electrolyte flow chamber (4) is provided with a reaction through hole connecting the anode end plate (1) and the cathode end plate (7); The negative end plate (7) has a hollow structure.

8. The electrolytic cell according to claim 7, characterized in that, The method for preparing the hydrophobic anode is as follows: A titanium substrate is subjected to constant current electrodeposition and a first calcination sequentially to obtain an anode electrode; the anode electrode is then coated with a hydrophobic agent and subjected to a second calcination sequentially to obtain a hydrophobic anode. The electrolyte for constant current electrodeposition comprises a metal precursor and a solvent. The metal precursor is chloroiridium acid and ruthenium chloride, and the molar ratio of chloroiridium acid to ruthenium chloride is 1:0.2~3. The solvent is one or two of methanol, ethanol, isopropanol and n-butanol. The concentration of the metal precursor in the electrolyte is 0.1~0.5 mol / L.

9. The electrolytic cell according to claim 8, characterized in that, The constant current electrodeposition temperature is 1~10℃, and the current density is 5~50mA / cm². 2 The time is 10-40 minutes; The first calcination temperature is 400~500℃, the time is 0.5~2h, and the heating rate to the first calcination temperature is 2~10℃ / min; the second calcination temperature is 250~500℃, the time is 0.5~2.5h, and the heating rate to the second calcination temperature is 2~10℃ / min. The hydrophobic agent is polytetrafluoroethylene, methyltrimethoxysilane, or polydimethylsiloxane, and the spraying amount of the hydrophobic agent is 0.05~1.0 mg / cm³. 2 .

10. The application of the electrolyzer according to any one of claims 7 to 9 in the degradation and removal of pollutants in water bodies.

Citation Information

Patent Citations

  • Carbon-based gas diffusion electrode and preparation method and application thereof

    CN116539688A

  • Carbon-based self-breathing cathode for in-situ production of hydrogen peroxide and degradation of organic matters and preparation method of carbon-based self-breathing cathode

    CN117721490A

  • Application of catalyst enhanced by three-phase reaction interface to improvement of activity and stability of electrochemically generated hydrogen peroxide

    CN118028894A

  • Preparation method of corrosion and scale inhibitor

    CN119570524A

  • Electrode for hydrogen peroxide production and its production

    JP2000256887A